PENDAMPINGAN INDUSTRI KECIL MENENGAH SIRUP PALA DI KOTA TERNATE - Ratri Retno Utami; Arni Pratama; Muh. Idham (Universitas Muhammadiyah Mataram, 2023)
Abstrak: Sari buah pala Miristika Sweat produksi PT Gosari, beredar di Ternate dalam jumlah terbatas karena belum optimalnya kapasitas produksi, serta belum mendapatkan izin edar MD dari BPOM . Permasalahan ini ditindaklanjuti dengan melakukan pendampingan selama bulan Agustus-November 2021. Tujuannya adalah untuk melakukan identifikasi permasalahan dan memberikan solusi atas permasalahan yang dihadapi PT Gosari. Metode pendampingan melalui observasi dan wawancara, pelatihan analisis organoleptik, dan pendaftaran merek serta NIB. Hasil uji keberterimaan konsumen menunjukkan bahwa Gosori cukup bersaing dan lebih diminati dibandingkan dengan sirup pala merek lain. Luaran yang telah tercapai yaitu, uji coba pasar, nomor pendaftaran merek, pelatihan penyuluhan sertifikasi pangan, serta telah melakukan migrasi NIB perusahaan berbasis resiko. Kegiatan selanjutnya akan difokuskan kepada produksi, penjualan, dan pengurusan ijin edar PIRT. Abstract: Miristika Sweat nutmeg juice produced by PT Gosari was marketed in Ternate in limited quantities due to not yet optimal production capacity and has not yet received an MD distribution permit from BPOM. This problem was followed up by assisting in August-November 2021. The aim was to identify problems and provide problem solutions for PT Gosari. Assistance methods through observation and interviews, organoleptic analysis training, and registration of brands and NIB. Based on the problem identification, it was necessary to change the term isotonic nutmeg extract to nutmeg syrup because nutmeg syrup only requires a distribution permit for PIRT, so Miristika Sweat's isotonic nutmeg extract was changed to Gosori nutmeg syrup. The results of the consumer acceptance test showed that Gosori was quite competitive and more desirable than other brands of nutmeg syrup. The outputs that have been achieved are market trials, brand registration numbers, food certification extension training, and risk-based company NIB migration. Future activities will be focused on production, sales, and distribution permits for PIRT.